Proliposomal Ropivacaine Oil: Pharmacokinetic and Pharmacodynamic Data After Subcutaneous Administration in Volunteers. (May 2016) - Ginosar, Yehuda; Haroutounian, Simon; Kagan, Leonid; Naveh, Michael; Aharon, Arnon; Davidson, Elyad M.
Abstract : BACKGROUND: Slow-release liposomal formulations of local anesthetics prolong plasma redistribution and reduce peak plasma drug concentration, allowing safer administration of larger doses and further prolonging sensory effects. However, their clinical applicability is limited by expensive manufacture and liposomal leakage. Previously, we described the simple preparation of a novel proliposomal ropivacaine oil that produces multilamellar liposomal vesicles on exposure to aqueous media and that has a shelf-life of >2 years at room temperature. In this study, we present both pharmacodynamic and pharmacokinetic data in healthy volunteers after subcutaneous injection of this novel proliposomal preparation of ropivacaine. METHODS: In the pharmacodynamic phase of this study, 15 volunteers received 3 separate subcutaneous injections of 2.5 mL containing 1 of the following drugs: proliposomal 4% ropivacaine, plain 0.5% ropivacaine, and the ropivacaine-free proliposomal vehicle. Drugs were administered into the lower back, and their location was randomized and blinded; a separate area was used as an uninjected, open control. Experimental sensory assessment was made at repeated intervals over 72 hours using both pinprick sensation and experimental heat pain tolerance (assessed using quantitative sensory testing). In a separate pharmacokinetic phase of this study, 9 volunteers received subcutaneous injections of 2.5 mL of either proliposomal 4% ropivacaine ( n = 6) or plain 0.5% ropivacaine ( n = 3); these participants had plasma ropivacaine concentrations assessed at repeated intervals over 72 hours. RESULTS: The mean ± SE duration of pinprick anesthesia after proliposomal and plain ropivacaine administration lasted 28.8 ± 6.0 and 15.9 ± 3.5 hours, respectively (mean difference, 16.8 hours; 95% confidence interval, 10.0–23.7; P = 0.001). For experimental heat pain, the anesthesia duration was approximately 36 and 12 hours, respectively, with mean ± SE area under the curve of the normalized heat pain tolerance over time 55.0 ± 28.8 Δ°C·min for proliposomal ropivacaine and 9.6 ± 26.0 Δ°C·min for plain ropivacaine (mean difference, 64.6 Δ°C·min; 95% confidence interval, 10.2–119.0; P = 0.036). In the pharmacokinetic study, there was no significant difference in peak plasma concentration in the proliposomal ropivacaine group (164 ± 43 ng/mL compared with 100 ± 41 ng/mL in the plain ropivacaine group; P = 0.07) despite an 8-fold increase in ropivacaine dose in the proliposomal group. The 99% upper prediction limit for peak plasma concentrations (351 ng/mL proliposomal; 279 ng/mL plain) was well below the putative toxic plasma concentration for both groups. The mean ± SE terminal half-life and area under the curve for proliposomal ropivacaine versus plain ropivacaine were 13.8 ± 3.6 hours vs 5.9 ± 2.3 hours ( P = 0.011) and 5090 ± 1476 h·ng/mL vs 593 ± 168 h·ng/mL ( P = 0.0014), respectively. CONCLUSIONS: The prolonged pharmacodynamic effect of proliposomal ropivacaine, together with its delayed elimination and prolonged redistribution to plasma, is compatible to depot-related slow-release and similar to the performance of other liposomal local anesthetics. The advantage of the proliposomal oil is its ease of preparation and its extended shelf-stability at room temperature. Abstract : Supplemental Digital Content is available in the text.